Analisis Strategi Untuk Pengembangan Usaha Usaha Mikro Kecil dan Menengah di Gresik Jawa Timur - Arif Syaifudin (Ecobuss, 2022)
Judging from the business competition in the snack food sector in Gresik, there are a lot of snack businesses that are open, causing intense competition. In addition, there are consumer tastes that are constantly changing and want healthy snacks with good quality and affordable prices so that UD. Nur Rohmah is required to provide something different from other snacks so that consumers can be loyal. The research was conducted with the aim of describing the strategies that have been implemented, to analyze the internal and external environment and to develop alternative business development strategies. The research was conducted at UD. Nur Rohmah Replaces Gresik. Data were collected through observation, document analysis, and interviews using the snowball sampling technique. The data analysis method was carried out using the SWOT analysis method (Strengths, Weaknesses, Opportunities and Threats). The results showed that by implementing a market development strategy using SWOT UD. Nur Rohmah has more customers and can open new branches to expand its market share in accordance with his vision. Keyword: MSMEs, Business Environment, SWOT Analysis, Business Development Strategies